2018
DOI: 10.1155/2018/2474831
|View full text |Cite
|
Sign up to set email alerts
|

Nephroprotective Effect of Zingerone against CCl4‐Induced Renal Toxicity in Swiss Albino Mice: Molecular Mechanism

Abstract: The protective effects of Zingerone against CCl4 induced nephrotoxicity in Swiss albino mice via modulation of metabolizing enzyme, oxidative stress, inflammatory cytokines, and apoptosis. The biochemical estimation indicated that the BUN and creatinine were significantly increased in group 2 (CCl4) compared to group 1 (normal) which was significantly reduced after treatment with Zingerone in group 3 when compared with group 2. The CCl4 treatment has significantly increased TBARS levels and reduced the antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
46
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 34 publications
7
46
0
1
Order By: Relevance
“…Several agents with potent antioxidant and anti-inflammatory activities exhibit protective effects against bleomycin-induced lung injury (4,19). Zingerone, as an interesting active ingredient of ginger (Zingiber officinale), exhibits potent antioxidant, anti-inflammatory, and anti-fibrotic activities in various animal models of disease (5)(6)(7)(8)20). However, its effect on pulmonary fibrosis has not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several agents with potent antioxidant and anti-inflammatory activities exhibit protective effects against bleomycin-induced lung injury (4,19). Zingerone, as an interesting active ingredient of ginger (Zingiber officinale), exhibits potent antioxidant, anti-inflammatory, and anti-fibrotic activities in various animal models of disease (5)(6)(7)(8)20). However, its effect on pulmonary fibrosis has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Zingerone, an active non-volatile ingredient of ginger (Zingiber officinale), has been known as a multi-target agent, displaying various pharmacological effects. For instance, zingerone exhibits antioxidant activity equal to ascorbic acid activity and can attenuate oxidative injuries in the lung (5), liver (6), and kidney (7). The protective effects of zingerone against lung injury induced by lipopolysaccharide (LPS) have been reported by suppressing neutrophil influx and production of proinflammatory cytokines in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Caspase‐3 was the main terminal shear enzyme in the process of cell apoptosis. When the intracellular Bax/Bax homodimer increases, Caspase‐3 could be activated and transform into Cleaved‐caspase‐3, then to trigger the downstream cascade reaction, destroy the integrity of DNA and lead to cell apoptosis (Wang, Zhang, Wang, Song, & Yuan, ; Cong et al., ; Jin et al., ; Safhi, ). In this study, we found that GMP‐Na 2 (250 mg/kg) could down‐regulated the expressions of Caspase‐3, Bax mRNA and protein in liver tissue of mice with AHI, and upregulated the expression of Bcl‐2.…”
Section: Discussionmentioning
confidence: 99%
“…The fourth group was injected intraperitoneally (IP) with CCl4 and treated with PPE, both as above. The dose of CCl4 and treatment period were based on previous studies (30)(31)(32). An equal quantity of olive oil was given IP to the control group.…”
Section: Gas Chromatography-mass Spectrometry (Gc-ms) Analysismentioning
confidence: 99%